2011
DOI: 10.1103/physrevb.83.144520
|View full text |Cite
|
Sign up to set email alerts
|

Josephson effect in S/F/S junctions: Spin bandwidth asymmetry versus Stoner exchange

Abstract: We analyze the dc Josephson effect in a ballistic superconductor/ferromagnet/superconductor junction by means of the Bogoliubov-de Gennes equations in the quasiclassical Andreev approximation. We consider the possibility of ferromagnetism originating from a mass renormalization of carriers of opposite spin, i.e. a spin bandwidth asymmetry. We provide a general formula for Andreev levels which is valid for arbitrary interface transparency, exchange interaction, and bandwidth asymmetry and analyze the current-ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 63 publications
3
32
0
Order By: Relevance
“…We can easily see than the period of Andreev level is 4π, which obeys the generate relation ε AR ∝ cos(φ/2) [21], while the period of ε AR /∆ s is 2π as shown in Fig.4, which is consistent with the results of Ref. [10]. We detect the effects of the electric field, off-resonance circularly polarized light, chemical potential, and length of the normal region to the Andreev bound level numerically.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…We can easily see than the period of Andreev level is 4π, which obeys the generate relation ε AR ∝ cos(φ/2) [21], while the period of ε AR /∆ s is 2π as shown in Fig.4, which is consistent with the results of Ref. [10]. We detect the effects of the electric field, off-resonance circularly polarized light, chemical potential, and length of the normal region to the Andreev bound level numerically.…”
Section: Resultssupporting
confidence: 89%
“…The reversal of the Josephson effect will be rised by the valley, spin, and pseudospin polarization, which with dramatic dipole oscillation between the two components induced by the off-resonance circularly polarized light as we have discussed [8], and results in a nonzero centerof-mass (COM) wave vector, just like the Josephson current realized by a ferromagnetic middle silicene (in superconductor/ferromagnet/superconductor ballistic Josephson junction [10]). It's found that the oscillation of valley polarization is related to the carrier-phonon scattering due to the photoexcitation which has a relaxation time in picosecond range [17] (since the frequency of light is setted in the terahertz range) and larger than that of the electron-eletron scattering.…”
Section: Andreev Bound Statementioning
confidence: 99%
“…The consequences of this have been addressed in the context of superconductor-ferromagnet proximity effect. 74 Although the barrier is spin-orbit coupled, this coupling will not lead to any spin Hall effects at the boundaries z = 0 and z = −a. Consequently, there is no accumulation of spin and the basic ballistic boundary conditions are identical to those in the theory of a conventional tunnel junction, namely:…”
Section: A Equations Of Motionmentioning
confidence: 99%
“…On solving the boundary conditions, we have 8 Andreev bound states given as E i (i = 1, ..., 8) = ±ε p (p = 1, ..., 4). From Andreev bound states energies [27] we get the Free energy of our system, which is given by [18]:…”
Section: Josephson Charge Currentmentioning
confidence: 99%